1995
DOI: 10.1016/s0022-5223(95)70003-x
|View full text |Cite
|
Sign up to set email alerts
|

Studies of hypoxemic/reoxygenation injury: Without aortic clamping

Abstract: This study tested the hypothesis that the developing heart is susceptible to oxygen-mediated damage after reintroduction of molecular oxygen and that this "unintended" reoxygenation injury causes lipid peroxidation and functional depression that may contribute to perioperative cardiac dysfunction. Among 49 Duroc-Yorkshire piglets (2 to 3 weeks old, 3 to 5 kg) 15 control studies were done without hypoxemia to test the effects of the surgical preparation (n = 10) and 60 minutes of cardiopulmonary bypass (n = 5).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 26 publications
0
39
0
Order By: Relevance
“…15 Resynthesis of ATP is delayed because of hypoxia during hypoxic reperfusion. 19 The finding that ATP levels are significantly depressed and ventricular function decreases during hypoxia parallel the findings seen clinically. 16 Excessive hypoxia during reperfusion may thus also result in poor recovery from ischemic injury.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…15 Resynthesis of ATP is delayed because of hypoxia during hypoxic reperfusion. 19 The finding that ATP levels are significantly depressed and ventricular function decreases during hypoxia parallel the findings seen clinically. 16 Excessive hypoxia during reperfusion may thus also result in poor recovery from ischemic injury.…”
Section: Discussionmentioning
confidence: 53%
“…16 Excessive hypoxia during reperfusion may thus also result in poor recovery from ischemic injury. 19 The experimental model used in our study has several limitations. First, we used a crystalloid solution in the perfusion circuit.…”
Section: Discussionmentioning
confidence: 99%
“…The immature heart has a higher tolerance to hypoxia, but preceding hypoxia prior to ischemic cardioplegic arrest results in poor functional recovery and is associated with derangements in several metabolites (19,23). Hypoxia also reduces the antioxidant reserve capacity, leading to a greater susceptibility to the oxidative stress of ischemia (e.g., cross-clamping of the aorta) and reoxygenation (12,18,38). Re-introduction of oxygen exacerbates this situation and eventually leads to a reduction in myocardial contractility (1,12,13,16,18,38).…”
Section: Discussionmentioning
confidence: 99%
“…Reoxygenation injury is associated with the production of reactive oxygen species by the formation of oxygen-derived free radicals such as superoxide and peroxide. This leads to cell membrane degradation through lipid peroxidation (12,18). It is now evident that oxidative stress is a major part of the cellular mechanism of the resulting myocardial damage (3,10,30,35).…”
Section: Discussionmentioning
confidence: 99%
“…Hypoxia per se does not raise the myocardial lipid peroxidation level, as shown in both our and other studies. 28,29 Ihnken et al reported that hypoxia increases cardiac susceptibility to oxidant damage by reducing antioxidants, and re-oxygenation further depletes the antioxidant level and accelerates lipid peroxidation. 28 Lipid peroxidation occurs by oxidation of PUFA in microsomal phospholipids.…”
Section: Discussionmentioning
confidence: 99%